"La Oliva". The Bridge between Two Generations - Martínez González, Xurxo (Madrygal. Revista de Estudios Gallegos, 2015)
The press provincialist 40s had several successors or followers. It highlights La Oliva (1856-1857), as it undoubtedly was the newspaper that best understands the legacy of the generation of 1846, both in politics and in the field of Galician culture. We aim to explain how La Oliva is a bond connecting the two generations and the role of Antolín Faraldo and Manuel Murguía.
Keywords: Provincialisme; press; Rexurdimento; identity; literature